Effects of different creep feeder designs and feed accessibility on creep feed consumption and litter performance - R C Sulabo; E J Wiedemann; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2007)
The objective of this experiment was to determine the effects of different creep feeder designs and increased feed accessibility on creep feed consumption and pre-weaning performance. A total of 54 sows (PIC Line 1050) and their litters were used in this study. Two groups of sows were blocked according to parity and date of farrowing using a randomized complete block design and allotted to three experimental treatments: Treatment 1 — rotary feeder with hopper (Control), Treatment 2 — rotary feeder without hopper, and Treatment 3 — pan feeder. A creep diet (1,585 kcal ME/lb, 1.56% TID Lys) with 1.0% chromium oxide was offered ad libitum at d 18 until weaning (d 21). A single lactation diet (1,586 kcal ME/lb, 0.97% TID Lys) was used, where sows were allowed free access to feed throughout lactation. Piglets were weighed individually at d 0 (birth), 18, and 21 (weaning) to calculate total and daily gains. Litter creep feed intake as feed disappearance was also calculated. Fecal samples from all piglets were taken twice using sterile swabs between 3 and 12 h before weaning for all treatments. Piglets were categorized as â€˜eaters' when the fecal sample was colored green at least once on any of the two samplings. Results showed no differences in pig (P<0.18) and litter (P<0.51) weights at weaning among litters using the different types of creep feeder. Total and daily gains of pigs (P<0.20) and litters (P<0.31) were also similar across treatments. Litters using the rotary feeder without the hopper or the pan feeder had 2.7 times greater (P<0.0001) total creep disappearance than those using the rotary feeder with the hopper. The average feeding frequency was 1, 2.3, and 4.2 times per 12 h for the rotary feeder with and without the hopper, and the pan feeder, respectively. Creep feeder design influenced (P<0.0001) the proportion of eaters created among piglets provided with creep feed. There were 69, 47, and 42% eaters in creep-fed litters using the rotary feeder with a hopper, rotary feeder without hopper, and pan feeder, respectively. In conclusion, the proportion of eaters in creep-fed litters can be influenced by non-dietary factors, such as creep feeder design.; Swine Day, 2007, Kansas State University, Manhattan, KS, 2007
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-121-S; Swine day; 2007; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 985; Swine; Feed management; Creep feed; Feeder design